A cross-level analysis of management commitment and work ability among senior casino dealers in Macau. Issue 5 (13th May 2019) - Li, Jun (Justin); Kim, Jong-Hyeong
Abstract : Purpose: This paper aims to investigate the corporate-level determinants (i.e. management commitment) of work ability. It also examined whether mid-level contextual variables intensify the relationship between management commitment and the work ability of senior casino dealers. Design/methodology/approach: A three-level hierarchical analysis of data from 432 casino dealers from 16 casinos was performed to determine the proportion of variance in the dependent variable when the explanatory variables were at varying hierarchical levels. Findings: The findings suggest that management commitment has a positive and significant impact on frontline dealers' work ability. Furthermore, supervisor support and group trust have moderating effects on the relationship between management commitment and dealers' work ability. Research limitations/implications: The current study provides important information on how to increase the ability of aging dealer to remain active and learn new skills. Originality/value: Work ability has received substantial attention from recent studies of human resources because of its close relationship to employee job skills and competencies. However, to the best of the authors' knowledge, no conceptual model explains the role of work ability role in promoting and updating human resources management practices and policies.